2015
DOI: 10.3109/0886022x.2014.1000802
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial nitric oxide synthase gene polymorphism with the risk of Henoch-Schönlein purpura/Henoch-Schönlein purpura nephritis

Abstract: Association between endothelial nitric oxide synthase (eNOS) gene polymorphism and Henoch-Schö nlein purpura (HSP)/Henoch-Schö nlein purpura nephritis (HSPN) risk is still controversial. A meta-analysis was performed to evaluate the association between eNOS gene polymorphism and HSP/HSPN susceptibility. A predefined literature search and selection of eligible relevant studies were performed to collect data from electronic database. Three articles were identified for the analysis of association between eNOS gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…While no genetic base has been suggested before for the FSD, recent studies evidenced a possible association between some genetic polymorphisms and the HSP. These polymorphisms are for example located in genes coding renin-angiotensin-system (RAS) components, endothelial nitric oxide synthases, Inter-Cellular Adesion Molecule 1, and Vascular Endotelial Growth Factor [10][11][12][13][14]. Also, MEFV, the gene responsible for the Familial Mediterranean Fever, could be a candidate gene for HSP [15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…While no genetic base has been suggested before for the FSD, recent studies evidenced a possible association between some genetic polymorphisms and the HSP. These polymorphisms are for example located in genes coding renin-angiotensin-system (RAS) components, endothelial nitric oxide synthases, Inter-Cellular Adesion Molecule 1, and Vascular Endotelial Growth Factor [10][11][12][13][14]. Also, MEFV, the gene responsible for the Familial Mediterranean Fever, could be a candidate gene for HSP [15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that the incidence of HSPN fluctuates between 20% and 80% [ 13 , 14 ]. Renal failure occurs in approximately 1%-12% patients with HSPN [ 15 ]. Previous studies have found that the incidence of HSPN is higher in the winter and spring, and is higher in men than in women, and this disease is most probably triggered by infection, which is in line with the findings of this study [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%